Challenging dominant sustainability worldviews on the energy transition: Lessons from Indigenous communities in Mexico and a plea for pluriversal technologies. (February 2022) - Velasco-Herrejón, Paola; Bauwens, Thomas; Calisto Friant, Martin
Highlights: Indigenous worldviews have much to offer regarding the sustainability debate. Indigenous and modernist visions of sustainability in the energy transition are analyzed. Different conceptualizations of sustainability must be recognized and integrated to ensure an inclusive and just energy transition. "Pluriversal technologies" are needed for a fair and sustainable ecological transition. Abstract: Little research exists on how alternative understandings of sustainability and societal well-being, such as those developed by marginalized Indigenous populations, can enrich and possibly challenge dominant visions of sustainability anchored in Western discourses on sustainable development and ecological modernization. This paper addresses this research gap in the context of the transition towards low-carbon energy sources by addressing the following question: how do Indigenous worldviews contrast with modernist visions of sustainability in the context of the energy transition? To do so, it first builds a conceptual framework contrasting modernist and Indigenous sustainability worldviews. Second, it applies this framework to the case of wind energy developments within the territory of three Zapotec communities located in southern Mexico, with the discussion relying on 103 interviews with key stakeholders, six focus groups and participant observation. Results show that the Zapotec sustainability worldview contrasts strikingly with wind developers' modernist propositions, which tend to reproduce the region's past colonial arrangements in terms of cultural domination, non-recognition of Indigenous identities and disrespect for local customs. This contrast has led to many conflicts and misunderstandings around wind energy projects. The paper concludes that different conceptualizations of sustainability must be recognized to ensure an inclusive and just energy transition, and advances the concept of "pluriversal technologies" to emphasize the need for technologies that embrace ontological and epistemological diversity by being co-designed, co-produced and co-owned by the inhabitants of the socio-cultural territory in which they are embedded.